Building Toward a Shared Culture Focused on Student Learning - Andrea Lassiter (Academic Chairpersons Conference Proceedings, 2016)
Revising or establishing student learning goals for a department can be a key point for driving change in curriculum, program structure, and faculty development. This session describes one department’s efforts toward culture change with student learning goals that feed higher level institutional objectives, comprehensive program assessment, and accreditation.
Keywords: Assessment; Program Outcomes; Learning Goals; Culture change